La mobilité du marché du travail : matériau pour une analyse socio-anthropologique des professions et catégories socioprofessionnelles - KOUIN, BARNABÉ JAURÈS (My University, 2021)
What future for the socio-professional categories in an economy and a society in profound mutations?That’s the question posed by the mobility of work and its world, characteristic of excessive globalization. Indeed, the central place that work, in the diversity of its forms, occupies for man and society has been called into question since the end of the last century with the emergence of new codes of work market access and new job categories. We are attending a categorical recomposition of work where some professional groups have disappeared to give birth to others. The sociodemographic variables are strongly correlating the supply of job which is coated in social inequity. By renewing the debate on the job crisis, the economic and social transformations have engendered a deconfiguration of economic activities by inducing a real overhaul of the work world with as a corollary a destructuration of the job structure.This article restores a survey that analyzes the anteriority of socioeconomic mutations to the deconfiguration of socio-professional categories in professional sphere in central and southern Benin. Thus, this paper aims, as a general objective, to examine the impact of changes of the work world in a globalized economy on socio-professional categories. Specifically, it involves, on the one hand, to inventory the various changes that have occurred in socio-professional categories and their effects and, on the other hand, to elucidate the process of the reconfiguration of the socioprofessional categories, which will lead us to explain the configuration of the new nomenclature of socio-professional categories.
Keywords: Mobility Of The Work World; Socio-; Professional Categories; Job Structure; Central And Southern Benin